Socialization of Banana Chip Marketing Strategy to Small and Medium-Sized Micro Entrepreneurs (MSMES) in Pandansarilor Kab. Malang Village by Students of KKN Group 06 UNISMA in 2018 - Mohammad Zulizar; Sukardi Abbas; Mawardi Djamaluddin (Archipelago, 2021)
Marketing management is the activity of analyzing, planning, implementing, and controlling programs that are structured in the formation, development and maintenance of profits from exchanges/transactions through target markets with the hope of achieving company goals in the long term (Assauri, 2013). ). MSMEs (Micro, Small and Medium Enterprises) are productive business units that stand alone, which are carried out by individuals or business entities in all economic sectors for economic development (Tambunan, 2012; Suci, 2017; Wibowo & Arifin, 2015; Susilo, 2012; Oktafia, 2017). Pandansari Lor Village, Jabung, Malang Regency which has extraordinary potential in agriculture, namely in the form of food crops, especially bananas and cassava, so it is known as the village that produces the largest food crops in Malang Raya. This can be proven from the high economic activity in the banana and cassava agricultural sector. However, in the midst of high economic activity, the MSME sector is not considered optimal enoughKEYWORDS: Marketing management, Pandansari Lor